Makna Tradisi Zakat Fitrah (Lawatino Pitaraa) dalam Pembentukan Karakter Kepedulian Sosial Masyarakat Etnik Muna - Wa Kuasa Baka; Usman Rianse; La Ode Topo Jers; Sitti Hermina; Samsul Samsul; La Ode Aris (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
This research aims (1) to explain the procedure for implementing the tradition of zakat fitrah (known as "lawatino pitaraa") in the Muna ethnic community, and (2) to discover and explain the wisdom and symbolic meanings inherent in the tradition of zakat fitrah's implementation in shaping the character of the Muna ethnic community. This study was conducted in Muna Regency, Southeast Sulawesi Province. The selection of informants was carried out using the snowballing technique. The data collection techniques used were: (1) direct observation, (2) in-depth interviews, and (3) literature study related to zakat fitrah. Qualitative descriptive data analysis was performed on the procedure for implementation and the symbolic meanings of zakat fitrah in the tradition of the Muna ethnic community. The research findings indicate that: (1) The implementation of "lawatino pitaraa" in the Muna ethnic group is led by a "modhi" who functions as the zakat administrator. The main stages of its implementation include: (a) the "muzakki" (the person giving zakat) handing over money according to their zakat obligation or substituting it with rice or corn; (b) the "muzakki" articulating their intention, (c) the "muzakki" grasping the rice or corn, (d) the turn of the zakat administrator to hold the rice or corn while simultaneously blowing on it with intention, (e) the zakat administrator leading a prayer to Allah SWT followed by the "muzakki"; (2) The significance of zakat fitrah's implementation in fostering the social concern character of the Muna ethnic group includes values of honesty/integrity, adherence to principles, surrender, inner peace, and submission to Allah SWT for the forgiveness of sins, purification of wealth, hope for a better future life, health, and longevity, as well as gratitude to Allah SWT. Zakat fitrah represents a social responsibility to create collective happiness among different social, cultural, and economic groups.